Diurnal Variations of Total Ozone Over Kathmandu Measured by Brewer Spectrophotometer - Chapagain, Narayan Prasad (Himalayan Physics, 2017)
This study presents the diurnal variations of atmospheric total ozone (or ozone content) measurements over Kirtipur, Kathmandu (27.67°N, 83.295°E) using a Brewer Spectrophotometer during a one-year period from February 2001 to February 2002. The measurements of ozone content were made only on daytime period. Result illustrates the significant diurnal variations of total ozone with maximum at near noon and minimum in the early morning and evening hours. The observed increase in total ozone around the noontime is about 5–10% of average ozone value. The monthly averages of total ozone for corresponding times are estimated from the selective days of good data set throughout the measurement period and then the seasonal averages of ozone for corresponding times are determined. The result clearly reveals seasonal diurnal variations of the total ozone with maximum averages values of ozone in spring and summer seasons and moderate in autumn, while minimum value in winter season. The Himalayan Physics Vol. 6 & 7, April 2017 (24-30)